(untitled) (Indian Journal of Nematology, 2024)
Plant parasitic nematodes (PPNs) and entomopathogenic nematodes (EPNs) are two major groups of nematodes of agricultural importance. PPNs are harmful to agriculture and cause damage to crops, whereas EPNs are beneficial as they kill cropdamaging insect pests. Understanding the population genetics of PPNs and EPNs helps identify the genetic diversity, origin, spread, and dispersal of these nematodes. Population genetics of PPNs and EPNs is poorly understood as compared to human or animal parasitic nematodes. Co-dominant and highly polymorphic microsatellite markers have proved to be the best candidates for studying the population genetics of the nematodes. The application of microsatellite markers in population structure analyses and to understand the phylogeography of various PPNs and EPNs is summarized in this review. This review also showcases the utility of microsatellite markers to understand the global spread of PPNs and EPNs and provides an insight into the role these markers may play in PPN management.